(untitled) (Jurnal Manajemen dan Ekonomi (JME), 2024)
Karang Taruna Tunjung Mekar, Macang Village, Bebandem District, Karangasem Regency, as one of the social organizations, is currently continuing to make efforts to develop public economic efforts by utilizing the potential and resources it has in efforts to process upakara waste. This is done with the aim of supporting and maintaining the existence and sustainability of the organization and developing an entrepreneurial spirit. Various activities are directed at developing public economic efforts, such as utilizing trash/remaining cultural waste into organic fertilizer, environmental management through waste banks, utilizing waste into handicrafts and so on. The limited knowledge and understanding of the administrators and members of youth organizations as an unproductive social group regarding the development of productive economic enterprises is a problem that must be solved. The aim of this research is to transfer technology through education and training and mentoring activities to increase knowledge, understanding, capacity and technical skills of youth organizations in developing productive public economic efforts. Assisting in the development and existence of youth organizations. This activity is carried out through counseling about the importance of developing productive economic businesses for youth organizations, as well as direct demonstrations of making organic fertilizer, handicrafts and waste banks by utilizing household waste and rubbish from around the environment. The results of the research show implications for increasing knowledge and capacity as well as skills of management and members of youth organizations in developing productive public economic efforts.